Internationalisation of the Malaysian Higher Education System Through the Prism of South-South Cooperation - Wan, Chang-Da; Sirat, Morshidi (International Journal of African Higher Education, 2018)
Many of the internationalisation eﬀorts in Malaysia have focused on enhancing collaboration with developed economies and Western systems. This article seeks to fll a gap in the literature by examining six initiatives to internationalise higher education within the Malaysian higher education system through the prism of South-South cooperation. It showcases the ways in which Malaysia participated in such initiatives and illustrates four levels of engagement ranging from government-to-government, institution-to-institution, international organisation-to-government using universities as intermediaries, and regional networks with Malaysian universities playing a signifcant role. Un grand nombre d’eﬀorts d’internationalisation de l’enseignement supérieur en Malaisie s’est concentré sur le développement de collaborations avec les économies développées et les systèmes occidentaux. Cet article cherche à combler une lacune de la littérature en examinant six initiatives visant à internationaliser l’enseignement supérieur au sein du système malaisien grâce à des coopérations sud-sud. Il expose l’engagement de la Malaisie dans de telles initiatives et illustre quatre niveaux d’engagement : intergouvernemental, interinstitutionnel, entre une organisation gouvernementale et un gouvernement en utilisant des universités comme intermédiaires et au sein des réseaux régionaux en donnant un rôle essentiel aux universités malaisiennes.